Self-Efficacy as a Mediator of Entrepreneurial Knowledge, Family Environment and Digital Literacy Effects on Green Entrepreneurial Intention - Ezar Shofi; Sandy Arief (Journal of Economic Education, 2026)
This study aims to examine the relationships between entrepreneurial knowledge, family environment, and digital literacy and green entrepreneurial intention through self-efficacy. The population of this study consisted of 10,123 students from the 2023 cohort of Universitas Negeri Semarang. The sample size was determined using the Slovin formula, resulting in 385 respondents. The sampling technique employed was proportionate stratified random sampling. Data were collected through questionnaires that had been tested for validity and reliability. The data analysis techniques included descriptive analysis and inferential analysis using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that (1) entrepreneurial knowledge, family environment, digital literacy, and self-efficacy have a positive and significant effect on green entrepreneurial intention; (2) entrepreneurial knowledge, family environment, and digital literacy have a positive and significant effect on self-efficacy; and (3) self-efficacy does not mediate the effects of entrepreneurial knowledge and family environment on green entrepreneurial intention. However, self-efficacy was found to mediate the effect of digital literacy on green entrepreneurial intention. This study is expected to contribute to the development of knowledge and provide empirical support for the Theory of Entrepreneurial Event and Social Cognitive Theory in explaining green entrepreneurial intention among university students.